Working Smarter Not Harder: Oxytocin Increases Domestic Dogs’ (Canis familiaris) Accuracy, but Not Attempts, on an Object Choice Task - Oliva, Jessica Lee; Mengoli, Manuel; Mendonça, Tiago; Cozzi, Alessandro; Pageat, Patrick; Chabaud, Camille; Teruel, Eva; Lafont-Lecuelle, Céline; Bienboire-Frosini, Cécile (Frontiers in Psychology, 2019)
The neuropeptide oxytocin (OT) has been shown to enhance dogs’ ability to perform an object choice task (OCT) involving the use of human pointing cues, when delivered intranasally. This study aimed at further investigating whether OT enhances task performance by increasing choices made, or by increasing correctness of choices made, and to compare these treatment effects to Dog Appeasing Pheromone (DAP), known to balance emotional activation in dogs. Hence, we compared OCT performance between three groups of dogs: i) dogs administered OT and a sham collar, ii) dogs administered a saline placebo and a DAP collar and iii) control dogs administered a saline placebo and a sham collar. All three groups consisted of a combination of male and female pet dogs and assistance-dogs-in-training currently living with a foster family. The study also evaluated the effect of intranasal OT and/or DAP on plasma levels of OT, and prolactin; which has previously been linked with anxiety in dogs. The dogs’ emotional state was measured using the Emotional Disorders Evaluation in Dogs (EDED) scale. The owners’ degree of anxious- and avoidant- style attachment to their dogs was accessed using the Pet Attachment Questionnaire (PAQ). Interesting descriptive data appeared for both treatment groups. Particularly, in OT group, we obtained significant results demonstrating that intranasal OT enhances OCT performance in dogs compared to control, by increasing the percentage of correct choices, but not the number of choices, made. Results also support that the mode of action of intranasal OT is via direct access to the brain and not via the blood, since no elevation of plasma OT (or prolactin) levels were observed after intranasal administration in this study. Similarly, DAP application did not significantly alter OT or prolactin peripheral concentrations. Several differences were observed between fostered and pet dogs, namely: fostered dogs demonstrated higher levels of serum prolactin, made more choices on the OCT compared to pet dogs but were not more likely to be correct, and were fostered by carers with higher avoidant attachment scores than pet dog owners. These findings implicate consideration of potential foster and training consequences for assistance dogs.